2013 IEEE International Symposium on Electromagnetic Compatibility 2013
DOI: 10.1109/isemc.2013.6670412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of loading on independent samples and uniformity of a reverberation chamber

Abstract: In order to understand the effects of loading on the estimation of independent samples and the consequent effect on the chamber uniformity, a series of measurements have been performed in a reverberation chamber with different sets of loads. The relationship between independent samples, loading and uniformity has been evaluated from the measured results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…10, the non-LoS unstirred component UC 2 contributes to the K-factor increase. Hence, mounting an absorber on the hatch door (where UC 2 is reflected from) lowers the RR [68] as can be seen in Fig. 12 (after the preloading).…”
Section: B Measurement Results and Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…10, the non-LoS unstirred component UC 2 contributes to the K-factor increase. Hence, mounting an absorber on the hatch door (where UC 2 is reflected from) lowers the RR [68] as can be seen in Fig. 12 (after the preloading).…”
Section: B Measurement Results and Analysismentioning
confidence: 88%
“…In [10], it is shown that slightly loading a VIRC with an absorber decreases its Q-factor and, thereby, broadens the resonance bandwidths. This consequently increases the modal overlap and ensures a better fit to the theoretical Rician distribution [68], i.e., a lower RR. On the other hand, care needs to be taken not to overload the chamber with absorbers, which can have negative effects on its reverberation properties [69].…”
Section: B Measurement Results and Analysismentioning
confidence: 99%
“…the intrinsic channel can be tuned to emulate a particular environment by loading the RC e.g. with absorbers [9,[18][19][20][21][22]. This allows to omit an additional CE [23].…”
Section: Eut With Integrated Antennamentioning
confidence: 99%
“…Moreover, as depicted in Figure 4.9, the non-LoS unstirred component, UC 2 , contributes to the K -factor increase. Hence, mounting an absorber on the hatch (where UC 2 is reflected from) lowers the RR [224] as can be seen from Figure 4.11 (after the preloading). At the same time, this will-to a large extent-not sacrifice the K -factor of the channel (see Figure 4.12).…”
Section: Measurement Results and Analysismentioning
confidence: 92%
“…This consequently 4. VIRC MEASUREMENT AND ESTIMATION METHODOLOGY increases the modal overlap and ensures a better fit to the theoretical Rician distribution [224], i.e., a lower RR. On the other hand, care needs to be taken not to overload the chamber with absorbers, which can have negative effects on its reverberation properties [225].…”
Section: Measurement Results and Analysismentioning
confidence: 99%